STUDI MENGENAI PROSES TERTANGKAPNYA DAN TINGKAH LAKU IKAN TERHADAP GILLNET MILLENNIUM DI PERAIRAN BONDET, CIREBON (Studies on Capture Process and Fish Behavior towards Millennium Gillnet in Bondet Waters, Cirebon) - Carolina C. Rakhmadevi Haluan; Ari Purbayanto; M. Fedi A Sondita (Bogor Agricultural University, 2012)
ABSTRACTThe millennium gillnet was recently adopted by Cirebon fishermen. Its use has been spread to other areas. Research on this type of gear is rare. The objectives of this research were: to investigate the effects of transparency on the fish behavior towards net panel of millennium gillnet; and to obtain the information on catch composition and the capture process of millennium gillnet. This research consisted of laboratory experiment and experimental fishing. The first objective was conducted in the laboratory experiment from August 2005 to March 2006 at Fish Behavior Laboratory, Tokyo University of Marine Science and Technology. The second objective was carried out in October to November 2006 in waters off Cirebon. This study concludes that: net transparency affected the Japanese Jack mackerel behavior towards contrast color net panel; the reduced transparency caused by the length of usage was not significant; catch of millennium gillnet in the field dominated by threadfins (71.29%) and the other catch were by-catch; and capture process of millennium gillnet dominated by gilled and wedged.Keywords: fish behavior, millennium gillnet, capture process, catch composition, contrast color——ABSTRAKGillnet milenium baru-baru ini telah diadopsi oleh nelayan Cirebon. Penggunaannya telah menyebar ke daerah lain. Penelitian pada jenis alat tangkap ini masih jarang dilakukan. Tujuan penelitian ini adalah menyelidiki pengaruh transparansi terhadap tingkah laku ikan pada panel jaring gillnet